The Effect of Supplementing Lignolitic Probiotic in Rice Straw on in Vitro Gas Production,Concentration of Ammonia (NH3),and Volatile Fatty Acid (VFA) - Prihartini, Indah; Ajeng Hariska, Viga (International Journal of Engineering & Technology, 2019)
The aims of this research were to know the effect of supplementing lignolitic probiotic in rice straw on in vitro gas production, concentration of ammonia (NH3), and VFA and to know the optimal use of lignolitic probiotic in rice straw. The materials used were rice straw and lignolitic probiotic. The methods used was Randomized Block Design (RBD) with 4 treatments and 3 groups. The treatments were P0: rice straw; P1: rice straw + 0.5% probiotic; P2 : rice straw + 1.0% probiotic; and P3: rice straw + 1.5% probiotic. The materials was incubated for 96 hours. The result showed that treatments significantly affected on in vitro gas production (P<0.01). Treatment of P3 had the highest gas production (73.86 ml/500mg DM) and VFA production (51.08 Mmol/l). While treatment of P0 had the lowest gas production (67.38 ml/500 mg DM) and VFA production (42.48 Mmol/l). Concentration of ammonia observed in all treatments were adequately support the ability of rumen microbes to digest fiber. Based on the result of this reserach, it could be concluded that supplementing 1.5% lignolitic probiotic (P3) achieved the highest gas production at 96 hour incubation (73.86 ml/500 mg DM).